Transendothelial electrical resistance measurement by a microfluidic device for functional study of endothelial barriers in inflammatory bowel disease - Li, Ya; Xu, Min; Zhu, Zhu; Xu, Feng; Chen, Bing (Frontiers in Bioengineering and Biotechnology, 2023)
Inflammatory bowel disease (IBD) is a chronic relapsing and remitting disease with a rising incidence globally. Circulating exosomes play great roles in IBD pathogenesis through exosomal cargoes, especially impacting the function of endothelial barriers. Transendothelial electrical resistance (TEER) measurement is a widely used non-invasive and label-free strategy to monitor endothelial barrier function in vitro. This study established a well-designed microfluidic device to monitor the TEER changes of endothelial cellular barrier on-chip after treated with exosome derived from IBD serum. The chip comprised two layers of microfluidic chambers with a top layer for the perfusion of medium to maintain the nutrition and pressure during cell culture, and a bottom layer for the extracellular matrix mimic using hydrogel, which are separated by a semipermeable membrane that permitted the formation of endothelial cell barrier. Four electrodes independent from the outlets were integrated to the chip for TEER detection. With this platform, significant decrease of TEER was detected, indicating that IBD serum exosomes impact the endothelial cellular barrier on-chip. Moreover, in vivo mouse models supported that IBD serum exosomes promote the severity of disease. Proteome profiling was also performed to analyze the exosomal protein cargoes and explore the novel regulators. The results demonstrate that this in-house customized microfluidic chip emulates the endothelial barrier microenvironment and enables TEER monitoring, and can be used to investigate endothelial barrier function in vitro.